In the moment of making History: The case of COVID-19 in Zambia (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This paper discusses the unfolding of COVID-19 in Zambia between March and August 2020. Zambians were aware that international networks would lead to Zambia being affected by a disease that had caused much devastation in China. The discussion also demonstrates the ambiguous nature of economic means for survival. Thus, the search for means of survival would also become transmission lines of a deadly disease. The state used a mixture of liberal and authoritarian ways to deal with the spreading of the infections. The pandemic revealed the inadequacy of medical facilities. The discussion combined limited oral information, newspapers and published primary sources.
Keywords: COVID-19; Pandemic; Multi-sector; Responses; Collaboration